Prenatal ultrasound diagnosis, associated anomalies and pregnancy outcomes of fetal right aortic arch - Xie, Yuting; Weng, Zongjie; Wang, Ronghua; Wu, Qiumei; Ling, Wen; Chen, Jinwen; Guo, Shan (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThe aim was to summarise the prenatal ultrasound characteristics, associated anomalies and pregnancy outcomes of fetal right aortic arch (RAA) and to discuss the value of prenatal ultrasound diagnosis and prognostic analysis.MethodsWe retrospectively analysed 157 cases of fetal RAA diagnosed via prenatal ultrasound in our hospital from October 2017 to October 2022. RAA features were characterised by comparing prenatal ultrasound data with anatomical casting results after pregnancy termination or postnatal imaging and surgical intervention to analyse the prognosis and misdiagnoses of fetal RAA.ResultsOf the 157 fetal RAA cases, 50 (31.8%) cases were isolated RAA and 107 (68.2%) cases were nonisolated RAA. In terms of typing, 78 cases (49.7%) of right aortic arch-aberrant left subclavian artery (RAA-ALSA) and 75 cases (47.8%) of right aortic arch-mirror branch (RAA-MB), 3 cases (1.9%) of right aortic arch-isolated left subclavian artery (RAA-ILSA) and 1 case (0.6%) of right aortic arch-isolated left innominate artery (RAA-ILINA) were identified, and the incidence of combined cardiac anomalies and chromosomal anomalies was significantly greater in the RAA-MB group than the RAA-ALSA group. The live birth rate was significantly lower in the nonisolated RAA group than the isolated RAA group, and the prognosis of RAA-MB was significantly worse than that of RAA-ALSA. Among the 76 surviving patients, 72 (94.7%) cases were correctly diagnosed via prenatal ultrasound, and 4 (5.3%) cases had missed diagnoses and misdiagnoses. Of the 81 terminated pregnancies, 19 cases received pathological anatomy or vascular casting, including 18 cases with results consistent with the prenatal ultrasound and 1 case with inconsistent results.ConclusionsPrenatal echocardiography is useful for diagnosing fetal RAA. It is also necessary to classify RAA types as accurately as possible and detect the presence of potential cardiac and extracardiac anomalies and genetic abnormalities, which facilitates prenatal counselling and prognostic assessment of fetuses with RAA.